An ontology for describing ETL patterns behavior - Oliveira, Bruno (2016)
The use of software patterns is a common practice in software design, providing reusable solutions for recurring problems. Patterns represent a general skeleton used to solve common problems, providing a way to share regular practices and reduce the resources needed for implementing software systems. Data warehousing populating processes are a very particular type of software used to migrate data from one or more data sources to a specific data schema used to support decision support activities. The quality of such processes should be guarantee. Otherwise, the final system will deal with data inconsistencies and errors, compromising its suitability to support strategic business decisions. To minimize such problems, we propose a pattern-oriented approach to support ETL lifecycle, from conceptual representation to its execution primitives using a specific commercial tool. An ontology-based meta model it was designed and used for describing patterns internal specification and providing the means to support and enable its configuration and instantiation using a domain specific language.